ASSA13-17-5 The Effects of National Transfer Network System For Congenital Heart Disease Children in Early Intervention and Comprehensive Treatment. (29th April 2013) - Hong, Liang; Zhang, Huili; Wang, Xu; Chen, Qiuming; Du, Junbao; Xu, Xuan; Zhang, Wei; Li, Ying; Liu, Fangchao; Wang, De; Yan, Hui; Liu, Tao; et al.
Abstract : Objective: To analysis the effects of early prognosis, safety and medical costs in congenital heart diseases (CHD) children transferred through the newly-built National Transfer Network System for Congenital Heart Disease Children (NTNS) to get emergency transferring. Methods: NTNS was founded by the National Center for Cardiovascular Disease (NCCD), combined with the major medical centre, which is based on the on-line network and covers most areas of China. NTNS has formed a CHD transferring and collaborative network. This system is based on the most experienced medical resources in Beijing and regional hospitals. In the meanwhile, the CHD database was established to exchange the medical files, records and photos among the collaborative health care facilities, making medical suggestions and decisions of transferring for further urgent surgical procedures decided by on-line medical councils for the severely sick CHD children even in the most undeveloped provinces. After the major operations, the CHD children who need the continuous recovery are discussed by the multi-disciplinary team on-line and the children will be transferred the proper health care centres for further treatment. All of these form a comprehensive CHD therapy system combined with early diagnosis, fast cooperative medical councils, emergent transferring, early intervention and postoperative rehabilitation among the medical centres. Results: NTNS has transferred 121 severely sick CHD children and run 143 distanced medical councils. These children's median age was 10 months (5.6, 21.0) with youngest age at 4 days, the mean hospital stays of them was 12.9 ± 4.8 days, which is much shorter than the children with same diagnosis in the same period of time transferred traditional ways. However, the post-operative PICU stays (p = 0.58) and hospital cost (p = 0.17) were no statistical differences. The out-patient treatment cycles and out-patient cost of the children in NTNS-transferred group were 2.7 days and 78234.43RMB, which were less than those in the children in the traditional group. Conclusions: The National Transfer Network System for Congenital Heart Disease Children has been founded as a safe and effective working platform, which provided the prenatal diagnosis, emergent transferring, early surgical intervention and post-operative rehabilitation. This system shortened the hospital stays, treatment cycles, medical cost with sharing the capital's experienced medical resources. NTNS will continue to provide the experiences in health policies and emergent transferring, which will bring more good results to the CHD children.